Opacidade contra-alimentadora no PE: análise por Marcação Comparativa (Revista de Estudos da Linguagem, 2007)
Recent generative phonology is witnessing a debate between severalproposals concerning the solution of the opacity problem. “Opacity”refers to generalizations that are not superficially detectable – whichare explained in derivational phonology by applying ordered applicationof rules. In Optimality Theory, the opacity issue attracts special interest,since this theory abandons rules altogether, such as intermediaterepresentations and derivational stages between input and output. Asfor the responses to the opacity issue, some propose a return in OTto derivational levels, similar to the components of Lexical Phonology(KIPARSKY, 2000; RUBACH, 2000; ITÔ; MESTER, 2003). Thesesolutions give up full parallelism, since evaluation of well-formedness isrealized in a staged form. Other solutions maintain parallelism and appealto other resources of the theory to account for the issue, like conjoinedconstraints (KIRCHNER, 1996; McCARTHY, 1999), specializationsof correspondence constraints (Sympathy Theory) or markednessconstraints (Comparative Markedness Theory). Some of these alternativesolutions are, in some way, derivational or almost derivational(MCARTHY, 2006, p.5), because they appeal to an intermediate formto influence the output. In this paper, we discuss two phenomenafrom European Portuguese in which interaction is opaque. The analysisis restricted to counter-feeding opacity and focalizes an accountaccording to Comparative Markedness (McCARTHY, 2002a). Additionally,we discuss some of the implications of this account, relative to theRichness of the Base postulate, and some predictions concerningthe possibility of interaction with other processes.